CERAMIC ARMOR WILL BE REPLACED BY COMPOSITE ARMOR VERY SOON* - Soeyatno Soeyatno (JURNAL KONVERSI, 2012)
Ceramic armors have existed for more than 30 years. They replaced the much heavier metal armor.One of the biggest producers of ceramic armor is Bittosi in Spain. It is a confidential product with no open promotion. Ceramic armor is the side products of Bitossi. Their main products are alubit liming and balls for ceramic industry, paint and pharmacy. Their ceramic armors have been used by many countries in Europe and by NATO. Actually, ceramic armor is still too heavy for soldiers since itweighs approximately 8.6 kg depending on size, and is still too rigid. Therefore, people are still looking for more convenientmaterials, which is resistant to shooting, flexible, and lighter.The answer is composite productdeveloped by De Staat Mijn-DSM Research Campus Geleen of the Netherlands, specialist in polymer research. They have proved it very successfully in shooting test. It is flexible and weighs only about one third of ceramic armor. The composite is produced from 20 layers of 0.15 mm thickPE (Poly Ethylene) sheets,reinforced by carbon fibers. Since it is far better than ceramic armor, the composite armor will replace ceramic armor very soon. It is only a matter of time. Keywords:ceramic armor, composite